Tobacco use and exposure to second-hand smoke among high school students in Ernakulum district, Kerala: A cross-sectional study - S. Aswathy; S. Syama; S. Georgy; M.M. Mathew; S. Mohandas; V.B. Menon; M. Numpelil (Elsevier, 2021)
Objectives: Tobacco use and exposure to second-hand smoke (SHS) in the home setting are major health hazards for adolescents. The objectives of this study were to estimate tobacco use and exposure to SHS among high school students in Ernakulam district of Kerala, India, and to investigate associated factors. Study design: Cross-sectional study. Methods: A school-based cross-sectional study was carried out in 25 randomly selected high schools from 210 schools in the Ernakulam educational district of Kerala, India. The minimum calculated sample size for ever-use of tobacco and SHS exposure was determined to be 2500, with 95% confidence interval (CI) and 10% relative precision. Data were collected using a semi-structured, pre-tested questionnaire from 2585 high school students. Data analyses were performed using SPSS version 20. Results: The ever-use of tobacco was reported to be 3.9% (95% CI 3.16 to 4.54) and the mean age of the participants was 13.97 ± 0.77 years. One-fifth of participants had tried a tobacco product before the age of 10 years. SHS exposure at home was reported by one in every 5 respondents (20.3%). Male gender (adjusted odds ratio [aOR] 8.79; 95% CI 3.16, 24.53), presence of a family member who smokes within the home (aOR 4.28; 95% CI 2.58, 7.12), lack of awareness about the harmful effects of SHS exposure (aOR 2.47; 95% CI 1.41, 5.18) and having seen an advertisement or promotion at point of sale (aOR 2.16; 95% CI 1.29, 3.60) were found to be independent predictors for tobacco use.Participants with respiratory infections were three times more likely to have experienced SHS exposure at home (aOR 2.87; 95% CI 2.21, 3.74), there was an 86% protective effect of SHS exposure for participants with a father in a professional occupation compared with unskilled profession (aOR 0.14; 95% CI 0.02, 0.67; p < 0.15) and participants with ever-use of tobacco were two times more likely to have experienced SHS exposure at home (aOR 1.63; 95% CI 3.13, 8.98). Conclusions: SHS exposure in the home environment continues to be high. Urgent innovative measures are necessary for the implementation of tobacco smoke-free homes and to reduce tobacco use in this vulnerable population. Further studies are necessary to determine ways to reduce smoking within homes and to increase population awareness.